THE DYNAMICS OF SUSTAINABLE CREATIVE CITY OF PEKALONGAN IN THE PERSPECTIVE OF COLLABORATIVE GOVERNANCE REGIME - Satrio Budi Adi; Effy Z. Rusfian; Martani Huseini (Jurnal Administrasi Profesional, 2025)
This study explores the dynamics of Pekalongan’s sustainability as a UNESCO Creative City through the lens of the Collaborative Governance Regime (CGR). The research addresses the complexity of governance arising from government dominance and the weak integration among the quadruple helix actors: academia, business, community, and government (ABCG). Using a qualitative interpretive approach with in-depth interviews involving 14 key informants, this study aims to analyze the driving elements that influence collaborative dynamics and to design an adaptive CGR model for creative city sustainability. The findings reveal that the sustainability of the creative city depends on the interaction between cultural capital, shared motivation, and principled engagement among stakeholders. Pekalongan’s creative ecosystem still faces fragmented collaboration and limited institutional capacity. However, enabling factors such as local cultural values and leadership commitment strengthen the collaborative process. The proposed CGR-based model emphasizes the importance of integrative and dynamic governance practices to enhance city resilience, inclusivity, and creative survivability. These findings contribute both conceptually and practically to the development of collaborative governance frameworks that support the Sustainable Development Goals (SDGs), particularly in fostering inclusive and sustainable urban development